Foreign Investment into Australia - Adam McKissack; Jessica Xu (The Australian Government, The Treasury, 2016)
Despite the essential contribution of foreign investment to Australia's economic growth and prosperity, the benefits of foreign investment are not well understood. This paper aims to provide further insights into foreign investment in Australia by examining the trends, the sources and the positive effects of foreign investment into Australia. The available data on foreign investment in Australia suggests a fairly consistent trend over time despite increases in the number of foreign investment applications received by the Foreign Investment Review Board.
Keywords: F21; O56; 330; foreign direct investment